Capacity Building Strategy for Increasing Economic Productivity of Small and Medium Industries - Rahmad, Rahmad; Yunimar, Yunimar; Prawira, Adi; nasfi, nasfi (International Journal of Indonesian Business Review, 2023)
Purpose – Research to determine the effect of increasing the Capacity of Small and Medium Industries (IKM) to increase the capacity and productivity of economic activities. Research in the city of Bukittinggi from July to October 2022. Methodology/approach – Descriptive qualitative research methods, interview analysis techniques, group discussion forums and the Delpi technique. First, interview 6 SMI actors, second, 5 expert informants and three government stakeholders. Findings – Research Findings The factors increasing IKM capacity are Capital, HR Quality, Facilities, Marketing, Production Quality, Financial Management, Technology, Promotion, Availability of Raw Materials and Environmental Support, the results of factors that greatly influence IKM capacity are HR Quality with a score of 5.00 or 100% with Very important criteria and results based on the Effectiveness Level of the government's response to the factor known that Capital has a high effectiveness of the government's response with a score of 4.20 or 84% with Effective criteria, while a low level of effectiveness of the government's response is Financial Management with a score of 2, 80 or 56% with Less Effective Criteria. Research results strategies, improving financial management, academic collaboration and information technology enhancement as well as increasing raw materials and government supervision.